1980
DOI: 10.1136/bmj.280.6213.514
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of venous thromboembolism after total knee replacement by high-dose aspirin or intermittent calf and thigh compression.

Abstract: Summary and conclusions A prospective study of patients undergoing total knee replacement was carried out by using a combination of 15I-fibrinogen scanning and phlebography, and showed a high incidence of venous thromboembolic disease (TE). Ventilation-perfusion lung scanning was performed to detect pulmonary emboli in most patients. High doses of aspirin and an intermittent low-pressure pneumatic compression device (IPCD) were effective, even in women, in preventing TE. Low doses of aspirin and placebo were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(71 citation statements)
references
References 10 publications
1
68
0
2
Order By: Relevance
“…Platelet affinity for collagen progressively increased in untreated patients, 78 per cent of whom subsequently developed DVT. Secondly, Salzman et al (1971) reported that the incidence of DVT in patients undergoing hip arthroplasty was reduced from 34 per cent to 9 per cent (p < 0'02) by aspirin prophylaxis, and similar results were reported in a study of subjects undergoing total knee replacement (McKenna et al, 1980). Thus, it appeared that the addition of aspirin might fu rther enhance the effectiveness of EPCC.…”
Section: Discussionsupporting
confidence: 53%
“…Platelet affinity for collagen progressively increased in untreated patients, 78 per cent of whom subsequently developed DVT. Secondly, Salzman et al (1971) reported that the incidence of DVT in patients undergoing hip arthroplasty was reduced from 34 per cent to 9 per cent (p < 0'02) by aspirin prophylaxis, and similar results were reported in a study of subjects undergoing total knee replacement (McKenna et al, 1980). Thus, it appeared that the addition of aspirin might fu rther enhance the effectiveness of EPCC.…”
Section: Discussionsupporting
confidence: 53%
“…In the 1970s and 1980s, a number of studies investigated the use of aspirin in THA, 10,[62][63][64][65] TKA, 66 and HFS. [67][68][69][70][71][72] Those studies used high doses of aspirin of up to 3.8 g daily.…”
Section: Aspirin Vs No Prophylaxis-initial Plus Extended Prophylaxis mentioning
confidence: 99%
“…900 patients undergoing arthroplasty or HFS compared mechanical compression to no thromboprophylaxis. 31,66,[76][77][78][79] Six used an IPCD, and one a venous foot pump (VFP). 77 The risk of bias varied.…”
Section: Mechanical Interventions Vs No Prophylaxisinitial Prophylaxismentioning
confidence: 99%
“…Taken in high dosage, aspirin is also effective in the prevention of diabetic retinopathy (24) and is known to reduce the risk of venous thromboembolism in susceptible (i.e., postoperative) patients (22,40). Indomethacin, a highly potent NSAID (55), is prescribed for conditions such as rheumatoid arthritis (50), ocular inflammation (21), and primary headache disorders (49).…”
mentioning
confidence: 99%